Digital exhibition of the bridge: a visual art documentation on expression during the pandemic / Suzlee Ibrahim… [et al.] - Ibrahim, Suzlee (Universiti Teknologi MARA, 2020)
The COVID19 outbreak all over the world has affected many people in various aspects of life; economically, physically, and emotionally. In response to the World Health Organization (WHO) in March 2020, Malaysia had announced the Movement Control Order (MCO) as a preventive measure to obstruct the spread of COVID19. This action had put even many more people into a state of depression due to loneliness, fear, and isolation. Artist, Suzlee Ibrahim, who understood the artists’ feelings of not being able to exhibit during this pandemic had initiated a digital exhibition called The Bridge. This digital exhibition aims to bring together artists from around the world who want to express their feelings during the pandemics as expressions of art. Communication and networking amongst the artists were made through emails, social media, and telephones. The artists sent their artworks through emails, which were then collected and sorted for the exhibition. In conclusion, The Bridge has successfully brought together one hundred and fifty artists from sixty countries to come together and support each other. The Bridge signifies the artists’ hope for a better future and a world without COVID19.